Nitidine Isolated from the Bark of Zanthoxylum myriacanthum and its Effects on NTERA-2 Cancer Stem Cells - Phuong, Trieu Ha; Quan, Pham Minh; Bach, Pham Cao; Tuyen, Tran Thi; Nga, Nguyen Phuong; Cuc, Nguyen Thi; Thao, Do Thi; Van, Nguyen Thi Hong (Planta Medica, 2025)
Nitidine (NIT) was isolated from the bark of Zanthoxylum myriacanthum and assessed for anti-proliferative effects on NTERA-2 cancer stem cells using 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide assay, spheroid assay, DNA and lysosome staining, flow cytometry, caspase assay, immunoblotting, and molecular docking studies. Moreover, nitidine suppresses stemness properties like in vitro tumorsphere forming, c-myc, Oct4, Nanog proteins of NTERA-2 cancer stem cells after 48-hour treatment. Nitidine selectively induced anti-survival activities by triggering the intrinsic apoptotic process through p53 signaling and lysosome-dependent cell death (LDCD). The mechanism of action of nitidine on cancer stem cells was also investigated using molecular docking studies to provide physical insights. Molecular docking studies revealed that nitidine induces LDCD by effectively inhibiting the MHR1/2 domain of the TRPM2 protein on liposome membrane. These results suggested the potential capacity of nitidine in inhibiting cancer stem cells or tumor-initiating cells for therapeutic cancer application.
Keywords: nitidine; Zanthoxylum myriacanthum; Rutaceae; NTERA-2; cancer stem cells; p53 signaling; lysosome-dependent cell death